Antarctic fungus proteases generate bioactive peptides from caseinate - Nascimento, Talita C.E.S.; Molino, João Vitor Dutra; Donado, Priscila R.S.; Montalvo, Gualberto S.A.; dos Santos, Wellington L.; Gomes, José Erick G. [UNESP]; Santos, João H.P.M.; da Silva, Roberto [UNESP]; Sette, Lara Durães [UNESP]; Pessoa Junior, Adalberto; Moreira, Keila Aparecida (Elsevier, 2021)
The extracellular serine protease produced by Acremonium sp. L1-4B isolated from the Antarctic continent, was purified and used for the proteolysis of bovine and caprine sodium caseinate. Protein hydrolysates were evaluated in vitro to determine their antioxidant and antihypertensive potential, and later characterized by mass spectrometry. Bovine and caprine hydrolysates produced over 24 h showed a higher content of copper chelation (25.8 and 31.2% respectively), also at this time the ABTS+• scavenging was 65.2% (bovine sample) and 67.5% (caprine sample), and bovine caseinate hydrolysate (8 h) exhibited higher iron chelation capacity (43.1%). Statistically (p < 0.05), caprine caseinate hydrolysates showed relatively higher antioxidant potential in this study. All hydrolysates showed antihypertensive potential; however peptides released from caprine caseinate after 8 h of hydrolysis were able to inhibit 75% of angiotensin-converting enzyme (ACE) activity. Nano-ESI-Q-TOF-MS/MS analysis prospected a total of 23 different peptide sequences in the bovine hydrolysate fraction, originated from the αS1- and β-casein chain, whilst in caprine hydrolysate, 31 sequences were detected, all from β-casein. The low molecular weight bovine and caprine hydrolysates obtained in this research have the potential to act in the prevention of disorders caused by oxidative reactions and in the regulation of blood pressure. These findings support the development of new functional food and nutraceutical formulations.
Keywords: Angiotensin-converting enzyme; Antarctic microorganism; Antioxidant peptides; Cow milk; Functional food; Goat milk; Hydrolysates